Fruits of the Amazonian Forest. Part II: Sapotaceae - Roosmalen, Marc G.M. von (Acta Amazonica, 2020)
Descriptions and line drawings of fruits and seeds from 153 woody species of the family Sapotaceae occurring in Amazonia are presented, along with their preferred habitat, distribution, habit and seed dispersal.